The Effectiveness of Mindfulness-based Cognitive Therapy on Increasing the Resilience Dimensions of Women Aged 20–40 in Isfahan City in 2016 - Karbasizadeh, Fatemeh (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Aim: The present study aimed at investigating the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) on increasing the psychological resilience dimensions of women aged 20-40 in Isfahan city in 2016. Material and Methods: This applied research was conducted on 30 women (15 subjects were assigned to experimental group and the remaining subjects were assigned to control group) visiting Ferdows Women’s Garden in Isfahan city during 2016. The experimental group received the psychological interventions of MBCT in eight 90-min sessions. Results: Both groups responded the resilience questionnaire before and after the interventions. The findings revealed that the change in some resilience dimensions was more for the experimental group than the control one. Regarding the effectiveness of mindfulness, paying attention to the psychological problems of women is a matter of great importance. Non-psychological therapies alone fail to provide women with the ability to cope with stressful conditions. Conclusion: Therefore, promoting women’s mental health may entail comprehensive attention.